Impacts of radical prostatectomy with emphasis on physical and psycho-socio-emotional declines: An integrative review - Weslley Barbosa Sales (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2023)
Introduction: Prostatectomy oncological surgery is necessary for the continuity of life, but it has physical consequences (momentary inability to drive, erectile dysfunction), emotional (anxiety about the diagnosis and the consequences of treatment, depression) and psychosocial (feeling of impotence, failure, loss of status in society), which may or may not be transitory.  Objective: to identify, through an integrative literature review, the biopsychosocial impacts of Radical Prostatectomy.  Methodology: This is an integrative literature review, which included articles related to the proposed theme, published between the years 2012 to 2022, available in full, without language restriction; in addition to theses, dissertations and monographs. For this, the PRISMA guidelines were used, as well as the PICO strategy for the best delineation of the research question and research theme.  Results and discussions: In view of the discussion, the study can respond to the objections raised by this research, and can show that the culture of masculinity, with regard to virility, strength, and better performance, composes risk factors for possible impacts on Quality of Life of men undergoing radical prostatectomy. These factors are intrinsically associated with the majority of relationships and characteristics represented by a man.  Final considerations: Psychoeducation and general guidelines on sexual and mental health should be carried out to patients who undergo radical therapies, such as radical prostatectomy, so that these patients can achieve coping strategies that make them feel better, contributing directly to the best quality of life, functional capacity, and their social relationships.